1999
DOI: 10.1074/jbc.274.13.9068
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Topology of Pmt1p, a Member of an Evolutionarily Conserved Family of Protein O-Mannosyltransferases

Abstract: The identification of the evolutionarily conserved family of dolichyl-phosphate-D-mannose:protein O-mannosyltransferases (Pmts) revealed that protein O-mannosylation plays an essential role in a number of physiologically important processes. Strikingly, all members of the Pmt protein family share almost identical hydropathy profiles; a central hydrophilic domain is flanked by amino-and carboxyl-terminal sequences containing several putative transmembrane helices. This pattern is of particular interest because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
100
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 54 publications
2
100
0
Order By: Relevance
“…Yeast strains were grown under standard conditions and transformed following the method of Gietz et al (27) with the yeast shuttle vectors pRS423 (28), YEp352 (29), pSB53 (19), pSB56 (18), PMT2-YEp352 (23), pVG13 (18), pSB114 (18), and the plasmids listed below. Standard procedures were used for all DNA manipulations (30).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yeast strains were grown under standard conditions and transformed following the method of Gietz et al (27) with the yeast shuttle vectors pRS423 (28), YEp352 (29), pSB53 (19), pSB56 (18), PMT2-YEp352 (23), pVG13 (18), pSB114 (18), and the plasmids listed below. Standard procedures were used for all DNA manipulations (30).…”
Section: Methodsmentioning
confidence: 99%
“…Its N terminus faces the cytoplasm whereas the C terminus faces the lumen of the ER. Two major hydrophilic domains that are located between transmembrane spans one and two (loop 1) and transmembrane spans five and six (loop 5), respectively, are oriented toward the ER lumen and are essential for Pmt1p activity (18,19). The replacement of invariant amino acid residues in these regions suggested that these segments are involved in the recognition and/or binding of protein substrates and/or catalysis (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hydropathy analysis (Kyte and Doolittle, 1982) of Um11220, Um10749, and Um05433 suggest that they conserve the characteristic structure of O-mannosyltransferase proteins of two large transmembrane domains, located in their N-and C-terminal regions and separated by a central hydrophilic region (Strahl-Bolsinger and Scheinost, 1999). In addition to the topological distribution, the putative U. maydis PMT proteins conserve the number of predicted transmembrane domains with respect to S. cerevisiae PMTs: 11 for Um11220 and nine for Um10749 and Um05433 (see Supplemental Figure 1 online).…”
Section: The U Maydis Pmt Family Consists Of Three Membersmentioning
confidence: 99%
“…PMTs have been identified and extensively characterized in yeast. In Saccharomyces cerevisiae, seven PMT family members (Pmt1p to -7p) are present (8,9) that are integral ER membrane proteins with seven transmembranespanning domains (12). Phylogenetic analyses indicate that the PMT family is subdivided into the PMT1, PMT2, and PMT4 subfamilies, whose members include transferases closely related to S. cerevisiae Pmt1p, Pmt2p, and Pmt4p, respectively (1,13).…”
mentioning
confidence: 99%